Pacheco, teórico, artista, maestro (1564-1644) Museo de Bellas Artes de Sevilla, marzo - junio 2016 - Méndez Rodríguez, Luis (Junta de Andalucia, Consejería de Cultura, 2016)
Exhibition catalog, including eight essays
Includes bibliographical references
Rückentitel: Francisco Pacheco. Teórico, artista, maestro
Keywords: Pacheco, Francisco / 1564-1644 / Exhibitions; Pacheco, Francisco -- 1564-1644; Painting / Spain / Andalusia / Pictorial works; Zeichnung; Fassmalerei; Theorie; Malerei; Maltechnik; Kunst; Spanien; Ausstellungskatalog; Ausstellungskatalog -- Museo de Bellas Artes -- 16.03.2016-12.06.2016 -- Sevilla